Emotional Intelligence Development In Daniel Keyes' Flowers For Algernon (1966): A Humanistic Psychological Approach - Marliyanto, Rahmad; , Drs. H. Abdillah Nugroho, M.Hum; , Mauly Halwat Hikmat, Ph. D. (2013)
The study is focused on whole needs of the major character from humanistic psychological perspective. The aim of the study is to show the human needs and emotional intelligence of Charlie Gordon in reaching his self- actualization. The object of the research is a science fictional novel entitled Flowers for Algernon (1966) by Daniel Keyes., in analyzing Flowers for Algernon novel, the writer uses qualitative method and humanistic psychology approach. The data sources consist of primary data and secondary data sources. The primary data source is the novel Flowers for Algernon itself and the secondary data sources are the other sources related to the analysis such as the author's biography, books of literary theory of the object and issue. The method of the data collection is descriptive analysis. The result of the research demonstrates the following conclusions. Firstly, literary works and psychological phenomena therefore have the same object, human being. Second, Daniel Keyes views that self- actualized person is fulfillment in doing the best. Third, Daniel Keyes pictures the experience and the struggle to achieve self- actualization by the major character. It shows that human will be motivated to attend his self- actualization after gratifying the lower needs (basic needs). A person will develop himself, to be what he wants to be and to reach the goal in life.